AB050. The role of c-met in the prognosis and clinicopathology of renal cell carcinoma: results from a single-center study and systematic review - Chen, Shouzhen (Transl Androl Urol, 2016)
OBJECTIVE: The c-met proto-oncogene pathway plays an important role in tumor progression of various cancers. However, the impact of c-met pathway on renal cell carcinoma (RCC) remains controversial. METHODS: The expression of c-Met in ten RCC tissues and matched adjacent normal tissues was determined by Western blot analysis. Tissue microarrays (TMAs) were used to assess the expression of c-Met in tumor tissues from 90 patients with RCC via the method of immunohistochemistry. The meta-analysis of similar studies was also performed. All 12 eligible studies including our results involving 1,136 patients were conducted. RESULTS: In our study, the protein levels of c-Met were increased in RCC tissues than in adjacent normal tissues in 80% (8/10) of paired RCC tissues. The expression of c-met was positively associated with high nuclear grade (P=0.008), high pT stage (P=0.002) and high AJCC stage (P=0.01). Multivariate analysis revealed that the high expression of c-Met was a significant and an independent predictor of disease-specific survival [hazard ratio (HR), 2.85; 95% confidence interval (95% CI), 1.21–6.70; P=0.017]. Meta-analysis revealed increased c-met expression in RCC tissues was closely correlated with high tumor grade(II-IV) [odds ratio (OR) 2.63, 95% CI, 1.68–4.12; P<0.001] and high pT stage(pT3 + pT4) (OR 2.19, 95% CI, 1.39–3.46; P=0.001). Most importantly, c-met expression significantly correlated to disease-speciﬁc survival (HR 1.50, 95% CI, 1.21–1.86; P<0.001). No heterogeneity and publication bias were observed across all studies. CONCLUSIONS: In RCC patients, c-Met is strongly associated with pathological grade, stage and disease-specific survival, which suggested that c-met might become a potential marker to predict patient prognosis and guide clinical diagnosis and treatment.